Novel pH-Responsive Structural Rearrangement of Myristic Acid-Conjugated Quetiapine Nanosuspension for Enhanced Long-Acting Delivery Performance - Nguyen, Hy Dinh; Ngo, Hai Van; Lee, Beom Jin (Advanced Science, 2024)
Quetiapine myristate (QM), an ester-bonded lipophilic prodrug of quetiapine (QTP), is synthesized and converted into an amphiphilic structure in acidic pH to trigger a novel self-assembled QM nanosuspension (QMN). Following injection, this QMN rearranges within physiological pH to form nanoaggregates in structure, resulting in enhanced physicochemical properties and in vivo therapeutic performance without an initial burst release. The 200-nm-sized QMN exhibits less invasive injection, higher drug content, and better storage stability profile than conventional poly(lactide-co-glycolide) (PLGA) nanosuspensions containing QTP or QM. Following a single intramuscular injection to beagle dogs (35 mg kg−1 QTP), QMN undergoes pH-responsive nanoaggregation to form the lipophilic prodrug, providing esterase-oriented sustained release for five weeks compared with the two-week period of PLGA nanosuspensions. Notably, QMN exhibits improved in vivo pharmacokinetic performance with long-acting delivery while minimizing issues associated with polymeric PLGA formulations, including the initial massive burst release, cellular toxicity, and adverse side effects. These results support the further development of QMN as a novel long-acting injectable to improve patient compliance and dosing frequency.
Keywords: Burst release; Initial burst release; Injectables; Long-acting injectable; Nanoaggregates; PH-responsive; Ph-responsive structural rearrangement; Quetiapine myristate; Self assembled nanoparticles; Structural rearrangement; Animals; Delayed-Action Preparations; Dogs; Drug Delivery Systems; Hydrogen-Ion Concentration; Male; Nanoparticles; Quetiapine Fumarate; Suspensions; initial burst release; long-acting injectables; nanoaggregates; pH-responsive structural rearrangement; quetiapine myristate; self-assembled nanoparticles